E-Maintenance Application: System Development - Yew, Lam Hong; MAHDIN, HAIRULNIZAM BIN (Applied Information Technology And Computer Science, 2023)
This is a project regarding development of mobile application E-Maintenance and this application is built for company that requires a lot of scheduled work. The main objectives are design and develop E-Maintenance system which include both android and website. The main scope for this system is company Mega Auto & Electrical Engineering to use our application to let admin make work order for user to follow up on their own. The main method used here is waterfall model where will conduct interview, draw Unified Model Language diagrams and sketch wireframes. The next thing after methodology is analysis and design where the E-Maintenance interface is built here. After the prototype is done the work will continue with implementation.